AN INTERLEGALITY-BASED ETHNOGRAPHY OF LIVING FIQH IN MINANGKABAU MARRIAGE PRACTICES - Wimra, Zelfeni; Budia Warman, Arifki; Bunaiya, Mahlil; Yazid, Mhd (AKADEMIKA: Jurnal Pemikiran Islam, 2025)
This article explores the issue of ethnographic-based interlegality of living fiqh in Minangkabau marriage practices. The purpose is to explain the uniqueness of negotiation and the embodiment of Islamic jurisprudence within Minangkabau socio-cultural settings. This study emphasizes the cognitive biases of the dichotomy between local-global, peripheral-central, and traditional-modern. The data examined came from the experience of the Minangkabau community in internalizing Islamic marriage law as a living legal practice, ranging from the marriage procedure, marriage contract, walimah, mediation, to divorce. This research collected, analyzed, and interpreted empirical legal data that reveals the integration of Islamic, customary and state legal norms in marriage practice. The findings of this study show the existence of a legal tripartite legal construction: first, the practice of customary marriage formed by Islamic jurisprudence. Second, the awareness of Islamic law is influenced by customary law. Third, the regulatory intervention of the state that wants the formation of harmonization between customs and Islam. This study has implications for living fiqh literacy which shows the universal principles of sharia law in cross-cultural life.